Phosphorous removal by electric arc furnace steel slag adsorption - Lim, J.W.*; Lee, K. F.*; Chong, Thomas S.Y.; Abdullah, L. C.; Razak, M. A.; Tezara, C.* (IOP Publishing, 2017)
As to overcome the eutrophication in lakes and reservoirs which is resulted from excessive input of phosphorus due to rapid urbanization or uncontrolled agricultural activities, Electric Arc Furnace steel slag (EAFS), a steelmaking by-product, in which the disposal of this industrial waste considered economically unfavourable yet it’s physical and chemical properties exhibits high potential to be great P adsorbent. The objective of this study was to identify most suitable mathematical model in description of adsorption by using traditional batch experiment and to investigate the effect on Phosphorus removal efficiency and Phosphorus removal capacity by EAFS adsorption through variation of parameters such as pH, size of slag and initial concentration of Phosphorus. Result demonstrated that, Langmuir is suitable in describing Phosphorus removal mechanisms with the Maximum Adsorption Capacity,